Challenging the "Jacks of all trades but masters of none" librarian syndrome - Fowler, George J., III, 1950-; Hines, Samantha (Emerald Publishing Limited, 2018)
Librarianship may be said to be facing an identity crisis. It may also be said that librarianship has been facing an identity crisis since it was proposed as a profession. With the advent of technology that lowers barriers to the access of information, the mission of a library has become indistinct. This volume will explore the current purpose of librarianship and libraries, how we become "Masters of our Domains", develop expertise in various elements of the profession, and how we extend outward into our communities.
Includes index.
Keywords: Library science.; Librarians.; Language Arts & Disciplines -- Library & Information Science -- General.; Library & information sciences.; elektronické knihy; electronic books